Brain Tumour Related Headache: Features, Pathophysiology and Management Strategies - Doruch, Patrycja; Senger, Michał; Rogacka-Pyrak, Karolina; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2023)
Introduction. Brain tumours constitute approximately 1% of all newly diagnosed cancers. Their manifestation typically involves headache, neurological impairment, focal onset seizures and syndromes related to tumour location. Severe headache presents as a prevailing symptom and occurs in over 50% of patients. Brain tumour associated headache exerts significant effect on quality of life in cancer patients. The following article aims to provide a comprehensive overview of most common and promising brain tumour related headache treatment strategies. State of knowledge. Headache in brain tumour patients arises from traction or displacement of intracranial pain-sensitive structures, such as vascular tissue, dura mater or periosteum. This can be caused by tumour’s mass itself, by tumour associated oedema or as a sequela of anti-tumour treatment. Most common therapeutic modalities include tumour surgical resection, cerebral oedema management, radiotherapeutic interventions and administration of analgesic agents. Complete removal of the tumour stands as the most effective approach, often bringing substantial alleviation in majority of cases. Conclusion. Headache affects the majority of individuals afflicted by brain tumours. Not all patients are suitable candidates for the resection of the underlying neoplasm. In such instances, the application of alternative approaches might be beneficial. Ongoing and future investigations may enhance the development of novel treatment strategies, possibly influencing the well-being of cancer patients, especially within palliative care area.